Using death certificate data to study place of death in 9 European countries: opportunities and weaknesses - Kaasa Stein; Addington-Hall Julia; Miccinesi Guido; Löfmark Rurik; Bilsen Johan; Cohen Joachim; Norup Michael; van der Wal Gerrit; Deliens Luc (BMC, 2007)
Abstract Background Systematic and reliable epidemiological information at population level, preferably cross-national, is needed for an adequate planning of (end-of-life) health care policies, e.g. concerning place of death, but is currently lacking. This study illustrates opportunities and weaknesses of death certificate data to provide such information on place of death and associated factors in nine European countries (seven entire countries and five regions). Methods We investigated the possibility and modality of all partners in this international comparative study (BE, DK, IT, NL, NO, SE, UK) to negotiate a dataset containing all deaths of one year with their national/regional administration of mortality statistics, and analysed the availability of information about place of death as well as a number of clinical, socio-demographic, residential and healthcare system factors. Results All countries negotiated a dataset, but rules, procedures, and cost price to get the data varied strongly between countries. In total, about 1.1 million deaths were included. For four of the nine countries not all desired categories for place of death were available. Most desired clinical and socio-demographic information was available, be it sometimes via linkages with other population databases. Healthcare system factors could be made available by linking existing healthcare statistics to the residence of the deceased. Conclusion Death certificate data provide information on place of death and on possibly associated factors and confounders in all studied countries. Hence, death certificate data provide a unique opportunity for cross-national studying and monitoring of place of death. However, modifications of certain aspects of death certificate registration and rules of data-protection are perhaps required to make international monitoring of place of death more feasible and accurate.